Associations of Visceral Adipose Tissue and Skeletal Muscle Density With Incident Stroke, Myocardial Infarction, and All‐Cause Mortality in Community‐Dwelling 70‐Year‐Old Individuals: A Prospective Cohort Study - Ballin, Marcel; Nordström, Peter; Niklasson, Johan; Nordström, Anna (Journal of the American Heart Association, 2021)
Background Aging leads to increased visceral adipose tissue (VAT) and reduced skeletal muscle density. To which extent these are associated with the risk of stroke, myocardial infarction (MI), and all-cause mortality in older adults is unknown. Methods and Results A total of 3294 70-year-old individuals (49.6% women) underwent a health examination in Umeå, Sweden, during 2012 to 2018. VAT and muscle density were measured using dual-energy x-ray absorptiometry and peripheral quantitative computed tomography. Cases of stroke, MI, and all-cause mortality were collected through national registers. Cox regressions were used to calculate hazard ratios (HRs) and 95% CIs per SD greater VAT and per SD lower muscle density. During a mean follow-up of 3.6 years, there were 108 cases of stroke or MI, and 97 deaths. Greater VAT (adjusted HR [aHR], 1.56; 95% CI, 1.09-2.22), but not lower muscle density (aHR, 1.14; 95% CI, 0.97-1.34), was associated with increased risk of stroke or MI. Neither VAT (aHR, 0.95; 95% CI, 0.65-1.41) nor muscle density (aHR, 1.11; 95% CI, 0.92-1.34) was associated with all-cause mortality. The association of VAT with stroke or MI was only significant in men (aHR, 1.86; 95% CI, 1.19-2.91) but not women (aHR, 0.60; 95% CI, 0.25-1.42) ( =0.038). Conclusions With the limitation of being an observational study, these findings suggest that VAT is an important obesity-related predictor of cardiovascular risk in 70-year-old men, and by implication, that decreasing VAT may potentially reduce their risk of cardiovascular disease.